Concepts for Integrating Music and Musical Tourism in Destination Growth (Vallis Aurea, 2023)
Purpose – The aim of the research is to analyze the possibilities of implementing music and musical tourism in innovating tourist offerings and promotions based on the results and systematic analysis of existing literature with specific application in the repositioning of Croatian tourism.Research Design – The conceptual research provides a comprehensive insight into the ways music is used in destination development. It focuses on various examples of implementing musical tourism.Methodology – The research includes bibliographic analysis using the Bibliometrix software package through the Scopus and WoS databases, which were selected to provide an overview of previous research on the concept of applying music in destination development, creating recommendations for implementation.Results – The results enable the identification of key determinants and concepts of musical offerings and promotions in Croatian tourism based on a systematic literature review and the specifics of Croatian tourism development at all levels.Research Originality – The application of music in tourism, music management in tourism – audio management, represents an insufficiently explored area of scientific and professional research and concrete applications in global and Croatian tourism. The paper provides specific proposals and research based on key research concepts. On an applied level, this requires a complete reevaluation of how destination tourism incorporates musical offerings into its development system.